2016
DOI: 10.1161/hypertensionaha.115.06177
|View full text |Cite
|
Sign up to set email alerts
|

Peri/Epicellular Protein Disulfide Isomerase Sustains Vascular Lumen Caliber Through an Anticonstrictive Remodeling Effect

Abstract: V ascular remodeling involves changes for the whole-vessel circumference and crucially determines lumen caliber 1 in physio(patho)logical situations, such as shear-stress responses, restenosis postangioplasty, 1-3 or native atherosclerosis. 1,4 Moreover, cellular mechanisms governing conductance vessel remodeling are likely shared by small-vessel remodeling, for example, in hypertension.5 Despite such relevance, mechanisms of vessel remodeling are not well known. The identification of endothelium 6 and nitric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 41 publications
3
44
0
7
Order By: Relevance
“…We had previously shown that csPDI is detectable in rabbit aorta segments in this condition [15]. However, given the lack of detectable soluble PDI secretion in cultured VSMC (Fig.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…We had previously shown that csPDI is detectable in rabbit aorta segments in this condition [15]. However, given the lack of detectable soluble PDI secretion in cultured VSMC (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…Moreover, little is known about pecPDI in vascular smooth muscle cells (VSMC). We previously reported that pecPDI exerts an anti-constrictive vascular remodeling effect during post-injury vessel repair in association with extracellular matrix and cytoskeleton reorganization in EC and VSMC, together with β1integrin thiol reduction [15]. Also, pecPDI neutralization in VSMC stimulates procoagulant microparticle release in P2rx7 –/– mice [23].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Este fato não surpreende, uma vez que a grande maioria dos genes microssintênicos e blocos genômicos regulados em eucariotos envolve genes ligados a desenvolvimento ou transcrição gênica (Irimia et al, 2013 RhoGDIα na camada íntima de vasos submetidos a remodelamento mediado por fluxo é consistente com os efeitos de PDIA1 observados previamente em nosso grupo. Estes incluem a migração e organização do citoesqueleto celular (Pescatore et al, 2012), bem como remodelamento vascular durante reparação à lesão e mecanoadaptação em resposta a estímulos biomecânicos (Tanaka et al, 2016). Os efeitos da PDIA1 na regulação do citoesqueleto celular parecem extrapolar o papel dessa PDI na regulação do complexo Nox NADPH oxidase, bastante estudado por nosso grupo e per se um sistema regulador do citoesqueleto (Moretti e Laurindo, 2016).…”
Section: Análises In Vitro Da Interação Entre Pdia1 E Rhogdiαunclassified
“…Estas observações vão ao encontro de vários outros resultados de nosso grupo indicando que PDIA1 exerce importante regulação da arquitetura do citoesqueleto (Pescatore et al, 2012; Moretti e Laurindo -em revisão) e do remodelamento vascular (Tanaka et al, 2016). Em conjunto, estes resultados reforçam significativamente a convergência funcional entre RhoGDIs e membros da família das PDIs, com implicações funcionais na organização do citoesqueleto e morfologia celular.…”
Section: Conclusõesunclassified